Savings Account Ownership During the Great Recession - Rhine, S.; Di, W.; Greene, William; Perlmeter, E. (Springer, 2016)
© 2016, Springer Science+Business Media New York.In the aftermath of the Great Recession, a substantial number of families were left financially at risk, especially those with lower income, less wealth, fewer years of education, and unstable employment. This study examined how families responded to the financial stresses of the Great Recession and found that families who were working age, had higher levels of education, and had become non-homeowners were more likely to maintain or open a basic savings account; whereas families who had lost a substantial amount of annual family income or wealth or were Black or Hispanic were more likely to have been without a savings account over the period. Insights from this study will help inform policymakers and others interested in encouraging family financial security and resiliency through basic savings accounts.